2012
DOI: 10.1111/j.1600-0536.2012.02170.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre study ‘rehabilitation of occupational skin diseases –optimization and quality assurance of inpatient management (ROQ)’–results from 12‐month follow‐up

Abstract: A randomized controlled trial would have been desirable, but was not possible, for legal and other reasons. However, the long-term 12-month follow-up shows that the TIP is associated with sustained improvements in terms of ability to work, QoL, and prognosis, and reductions in days of absence from work because of skin conditions and topical corticosteroid application. These results indicate that the TIP provided a reduction in the personal and public burden of OSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 25 publications
8
80
0
10
Order By: Relevance
“…These data confirm severity and chronicity of CHE in affected patients. In Germany the social security system covers treatment of severe occupational skin disease (OSD) by means of interdisciplinary in-patient rehabilitation measures with the goal of avoiding loss or change of job (16,17). The comparatively high figure for in-patient treatment can thus be explained by the fact that specialized centres for occupational dermatology offering such rehabilitation measures contribute significantly to the CARPE registry.…”
Section: Discussionmentioning
confidence: 98%
“…These data confirm severity and chronicity of CHE in affected patients. In Germany the social security system covers treatment of severe occupational skin disease (OSD) by means of interdisciplinary in-patient rehabilitation measures with the goal of avoiding loss or change of job (16,17). The comparatively high figure for in-patient treatment can thus be explained by the fact that specialized centres for occupational dermatology offering such rehabilitation measures contribute significantly to the CARPE registry.…”
Section: Discussionmentioning
confidence: 98%
“…This 12-month follow-up study revealed the persistence of the previously reported more immediate reductions in severity of OSD, topical steroid use, and number of days of absence from work and improvements in quality of life. These results indicated that the tertiary individual prevention [dermatological treatment and diagnostic procedures and patient education (health and psychological)] provided a reduction in the personal and public burden of OSD [34].…”
Section: Management and Preventionmentioning
confidence: 92%
“…The worker may need to receive workers' compensation and disability benefit after establishing occupational causation while considering retraining for a new job. The cost of early consideration for rehabilitation may be financially beneficial (Weisshaar et al, 2013;Van Gils et al, 2012a,b;Gomez et al, 2011;Holness, 2003).…”
Section: Rehabilitationmentioning
confidence: 98%